Non-iterative moment capacities of complex composite beams using Fourier series - Mohd Yassin, A.Y. (SpringerOpen, 2017)
A generic procedure is formulated for the determination of the moment capacity of composite beams having a complex cross-section. The key feature is the use of Fourier series to convert the piecewise functions of the cross-sectional stress distribution into a single-rule function. This eliminates the need for several capacity expressions to cover different stress stages, since the procedure permits the use of the general moment capacity expression. It also eliminates any iteration process when determining the location of the neutral axis since equilibrium of the cross-section can be satisfied explicitly. Numerical examples are given to demonstrate the validation and the applications of the formulation. © 2016, The Author(s).